Diplomasi Budaya Indonesia Melalui Gamelan: Studi Tentang Peran American Gamelan Institute (AGI) Dalam Mempromosikan Budaya Indonesia di Amerika Serikat Tahun 2019–2022 - Wahidin, Ihsan (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This research aims to study Indonesian cultural diplomacy through the art of gamelan as an instrument of soft power in strengthening the image of Indonesia in the United States, with a focus on the role of the American Gamelan Institute (AGI) during 2019–2022. The background of this research is based on the importance of culture as a strategic tool in international relations, especially in building international mutual understanding amidst the limitations of formal political diplomacy. The gamelan, as Indonesia’s world-class cultural heritage, became a representative symbol in that effort. In this study a qualitative approach with descriptive method of analysis was used. Data were collected through literature study, documentation, and interviews with relevant parties, such as representatives of AGI and the Ministry of Education and Culture. Research highlights AGI’s programs such as concerts, workshops, and cultural collaborations that successfully expanded the American public’s understanding of Indonesian culture. In addition, the study also identified various challenges faced, such as funding constraints, cultural differences, as well as lack of active participation on the part of Indonesia.The results show that although AGI is an organization pioneered by the American community, its existence is very strategic to support Indonesian cultural diplomacy. The support of the Indonesian government and the role of Indonesian cultural actors need to be enhanced for this cultural diplomacy to be more optimal in creating Indonesia’s image in the eyes of the world. This research contributes to the development of international relations studies, particularly the fields of cultural diplomacy and public diplomacy.